Legal Traps in a Sea of Oil: Uncovering Alleged Import Corruption by Pertamina Patra Niaga - Siahaan, Arie Kornelius Immanuel; Arifin, Ridwan (Law Research Review Quarterly, 2025)
This study investigates the alleged corruption involving oil importation by Pertamina Patra Niaga, a subsidiary of Indonesia’s state-owned energy giant, through a juridical analysis grounded in the Anti-Corruption Law (UU Tipikor) and the newly revised Indonesian Criminal Code (KUHP Baru). The research aims to explore how current legal frameworks respond to complex corporate corruption schemes, particularly in the energy sector, which plays a critical role in national economic stability and sovereignty. Using a normative legal method with a statutory and case-based approach, this study examines the legal classification, potential liability, and gaps in enforcement related to the alleged misconduct. It also evaluates the interplay between corporate responsibility and individual accountability under both the old and new legal regimes. Findings suggest that while the UU Tipikor provides a robust foundation for prosecuting corruption, the KUHP Baru introduces nuanced provisions that could either strengthen or complicate efforts to hold corporate actors accountable contribution of this research lies in its critical assessment of the effectiveness and limitations of Indonesian anti-corruption legislation in addressing large-scale, state-linked economic crimes. By dissecting the legal implications of the Pertamina Patra Niaga case, this study provides actionable insights for law enforcement agencies, policymakers, and legal scholars in designing more transparent, enforceable mechanisms for combating corruption in strategic sectors. Ultimately, it underscores the urgent need for aligning regulatory practice with the evolving complexities of corporate crime in Indonesia’s energy landscape.